Effectiveness of School Policies in Improving Quality Through the School-Based Management Approach - Frudensia Mawar Hure; Alpino Susanto; Zulkifli Zulkifli (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to analyze the effectiveness of school policies in improving quality through the School-Based Management (SBM) approach. The method used was mixed methods with an explanatory sequential research design. The first stage was conducted using a quantitative approach, with a Likert-scale questionnaire administered to parents of students (n = 100), and the survey data were analyzed descriptively. The second stage was conducted using a qualitative approach, with interviews to explain the findings from the quantitative data. The results of the study show that the average score of School-Based Management (SBM) implementation was 3.97 (moderate category), with leadership and decision-making scoring 4.16 as the strongest aspect, curriculum and learning management scoring 4.11 in the good category, evaluation and quality improvement scoring 3.98 in the moderate category, financial and facilities management scoring 3.97 in the moderate category, while parental and community participation scored 3.63 in the moderate category. This study indicates that School-Based Management at SMA Ananda Batam plays a strategic role in improving quality through the principal’s leadership in decision-making, while parental and community participation still needs to be improved through communication forums with a hybrid system. The driving factors for the implementation of School-Based Management include the principal’s transformational-democratic leadership style and a flexible and innovative curriculum, while the inhibiting factors include the absence of a quality assurance team, limited training for improving teachers’ competencies, insufficient maintenance of facilities and infrastructure, and limited communication between parents and the school